Applying Ã¢â‚¬Å“Make a MatchÃ¢â‚¬Â Model-based on Scientific Approach through Reward Education Game for Elementary School Students - Herwulan Irine Purnama (International Journal of Theory and Application in Elementary and Secondary School Education, 2022)
The main purpose of this study is to analyze how students learn by using the "Make a Match" and "Reward Education Games" strategies. This type of research is Classroom Action Research (CAR), where the teacher is the implementer and the researcher. Subject This research is a student of class VI A SD Negeri 37 Pontianak Southeast consisting of 26 students. The object of research is active learning and student learning outcomes. Data collection techniques using structured observation and field notes. Data were analyzed descriptively and presented in the form of diagrams. The results of the research obtained are learning by innovating the development of a scientific approach that is integrated with "Make a Match" and "Reward Education Games" that are did well to increase the students learning activities of class VI at SDN 37 Southeast Pontianak. Another result is the absorption of students in learning, students get scores above the KKM reaching 84.6%.